Short Communication: Variations of morphology, anatomy, and metabolite profiles of Citrus reticulata Blanco cv. Tawangmangu grafts produced by shoot tip grafting using several rootstocks - Einstivina Nuryandani; Ratna Susandarini; Ari Indrianto; Tri Rini Nuringtyas; Artnice Mega Fathima; Siti Subandiyah (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Nuryandani E, Susandarini R, Indrianto A, Nuringtyas RT, Fathima AM, Subandiyah S. 2020. Short Communication: Variations of morphology, anatomy, and metabolite profiles of Citrus reticulata Blanco cv. Tawangmangu grafts produced by shoot tip grafting using several rootstocks. Biodiversitas 21: 4671-4676.  Cultivation of Citrus reticulata Blanco cv. Tawangmangu, one of leading mandarin cultivars in Indonesia, remains challenging due to the limitations of suitable rootstocks. The use of suitable rootstocks will greatly determine the success of grafting and affect the performance of the scion. This study aimed to evaluate the morphological, anatomical, and metabolic profiles of grafts between Tawangmangu and rootstocks from various species using shoot tip grafting. Observations of morphological, anatomical, and metabolite variation were carried out eight weeks after the beginning of the growth of the scions. The morphological characters were observed on leaves and stems of the scions. Anatomical data were obtained from the examination of longitudinal sections of grafts prepared using paraffin-embedded method. Analysis of metabolite profiles was performed using LC-MS. The results showed that for two of the three rootstocks used, C. ichangensis × C. reticulata cv. Austera (Japansche Citroen (JC)) and Citrus (Fortunella) japonica (Fortunella) scion growth was vigorous and resulted in a large number of leaves and long stems. Morphological variation was found in the leaf shape, as indicated by wider and wavy leaves of grafts with Fortunella, while narrower and straighter leaves were found in grafts with JC. The grafting onto the third rootstock, C. hystrix, induced dwarfing of the scions. Variation in the anatomical profiles was found in vascular vessels, and in exodermic and endodermic cell sizes. Differences in metabolic profiles of the grafts were found compared to scion and rootstocks. Results of this study provide an important contribution to the successful improvement of Tawangmangu.